Penerapan Model Problem Based Learning Untuk Meningkatkan Pemahaman Dan Keimanan Siswa Terhadap Nabi Dan Rasul Allah di Kelas V III-1 SMPN 3 Lubuk Sikaping - Saputra, Dedi (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This study aims to improve students’ understanding of the topic "faith in prophets and messengers of Allah" through the implementation of the Problem-Based Learning (PBL) model. The classroom action research was conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The results indicate that in Cycle I, student participation was low, and most students did not meet the minimum competency standards. In Cycle II, improvements were made, including intensive guidance, the use of interactive media, and varied teaching methods, leading to significant progress in student learning outcomes. Most students achieved the minimum competency standards, with higher average scores compared to Cycle I. This study concludes that Problem-Based Learning is effective in enhancing students’ understanding of faith-based topics while fostering critical thinking and collaboration skills.